An Evaluation of the Protein Digestibility of Flours and Derived Protein Rich Product of Three Varieties of Mucuna Pruriens (L.) From Rats (Rattus Norvegicus) Males in Growth - Théopihile, Maoudombaye; Ali, Mahamat Seid; Doloum, Gomoung; Josiane, Ngatchic Metsagang Therese; Ndoutamia, G. (International Journal of Applied Sciences and Biotechnology, 2017)
The objective of the present study is to evaluate the proteinaceous digestibility of crude flours and derived protein rich product of three varieties of Mucuna pruriens of the male albino rats in growth. 48 rats have been taken randomly split up into 8 groups where 6 each according to their formulated feedings; those foods are: foods without protein (RSP), foods with casein (RC), food with the black macuna derived protein rich product (RMNc), food with the scratch macuna derived protein rich product (RMRc), food with the white macuna derived protein rich product (RMBc), food with the black macuna crude flours (RMNf), food with the scratch macuna crude flours (RMRf) et food with the white macuna crude flours (RMBf). All those foods content the same quantity of azote excepted foods without protein. Rats have been isolated in the semi metabolic cages which allow gathering the remaining of the foods supplied and the faeces to determine the parameter values of consumption. The experiment has taken 28 days. The apparent and reel protein digestibilities obtained in each food are respectively : RC (76,63±0,36% ; 95,86±0,06%), RMNc (71,20±0,77% ; 91,60±0,99%), RMRc (73,68±0,23% ; 93,49±0,85%), RMBc (71,16±0,59% ; 92,03±0,70%), RMNf (33,25±1,91% ; 53,881±1,70%), RMRf (31,3±2,40% ; 52,12±2,22%) and RMBf (31,12±4,00% ; 51,92±3,8%). The results show that derived protein rich product have ameliorated the protein digestibility and could be the alternative for the use of seeds of Mucuna pruriens to feed human beings and animals. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 284-292